Catastrophic Drought in the Afro-Asian Monsoon Region During Heinrich Event 1 - Stager, J. Curt; Ryves, David B.; Chase, Brian M.; Pausata, Francesco S. R. (Science, 2011)
An extreme megadrought occurred in the Afro-Asian monsoon region during an iceberg melting episode 50,000 years ago. , Between 15,000 and 18,000 years ago, large amounts of ice and meltwater entered the North Atlantic during Heinrich stadial 1. This caused substantial regional cooling, but major climatic impacts also occurred in the tropics. Here, we demonstrate that the height of this stadial, about 16,000 to 17,000 years ago (Heinrich event 1), coincided with one of the most extreme and widespread megadroughts of the past 50,000 years or more in the Afro-Asian monsoon region, with potentially serious consequences for Paleolithic cultures. Late Quaternary tropical drying commonly is attributed to southward drift of the intertropical convergence zone, but the broad geographic range of the Heinrich event 1 megadrought suggests that severe, systemic weakening of Afro-Asian rainfall systems also occurred, probably in response to sea surface cooling.

Tropical cyclone activity enhanced by Sahara greening and reduced dust emissions during the African Humid Period - Pausata, Francesco S. R.; Emanuel, Kerry A.; Chiacchio, Marc; Diro, Gulilat T.; Zhang, Qiong; Sushama, Laxmi; Stager, J. Curt; Donnelly, Jeffrey P. (Proceedings of the National Academy of Sciences, 2017)
Significance Our modeling study shows the crucial role of vegetation cover over the Sahara and reduced dust emission in altering tropical cyclone activity during the mid-Holocene (6,000 yBP). Our results also demonstrate how these regional changes in land cover and dust emission are able to affect areas far afield through changes of large-scale atmospheric circulation. Our study strongly suggests that an appropriate representation of land cover and dust emission is of paramount importance to be able to capture past—and potentially future—climate changes. , Tropical cyclones (TCs) can have devastating socioeconomic impacts. Understanding the nature and causes of their variability is of paramount importance for society. However, historical records of TCs are too short to fully characterize such changes and paleo-sediment archives of Holocene TC activity are temporally and geographically sparse. Thus, it is of interest to apply physical modeling to understanding TC variability under different climate conditions. Here we investigate global TC activity during a warm climate state (mid-Holocene, 6,000 yBP) characterized by increased boreal summer insolation, a vegetated Sahara, and reduced dust emissions. We analyze a set of sensitivity experiments in which not only solar insolation changes are varied but also vegetation and dust concentrations. Our results show that the greening of the Sahara and reduced dust loadings lead to more favorable conditions for tropical cyclone development compared with the orbital forcing alone. In particular, the strengthening of the West African Monsoon induced by the Sahara greening triggers a change in atmospheric circulation that affects the entire tropics. Furthermore, whereas previous studies suggest lower TC activity despite stronger summer insolation and warmer sea surface temperature in the Northern Hemisphere, accounting for the Sahara greening and reduced dust concentrations leads instead to an increase of TC activity in both hemispheres, particularly over the Caribbean basin and East Coast of North America. Our study highlights the importance of regional changes in land cover and dust concentrations in affecting the potential intensity and genesis of past TCs and suggests that both factors may have appreciable influence on TC activity in a future warmer climate.

Greening of the Sahara suppressed ENSO activity during the mid-Holocene - Pausata, Francesco S. R.; Zhang, Qiong; Muschitiello, Francesco; Lu, Zhengyao; Chafik, Léon; Niedermeyer, Eva M.; Stager, J. Curt; Cobb, Kim M.; Liu, Zhengyu (Nature Communications, 2017)
Abstract The evolution of the El Niño-Southern Oscillation (ENSO) during the Holocene remains uncertain. In particular, a host of new paleoclimate records suggest that ENSO internal variability or other external forcings may have dwarfed the fairly modest ENSO response to precessional insolation changes simulated in climate models. Here, using fully coupled ocean-atmosphere model simulations, we show that accounting for a vegetated and less dusty Sahara during the mid-Holocene relative to preindustrial climate can reduce ENSO variability by 25%, more than twice the decrease obtained using orbital forcing alone. We identify changes in tropical Atlantic mean state and variability caused by the momentous strengthening of the West Africa Monsoon (WAM) as critical factors in amplifying ENSO’s response to insolation forcing through changes in the Walker circulation. Our results thus suggest that potential changes in the WAM due to anthropogenic warming may influence ENSO variability in the future as well.